2008
DOI: 10.1021/ja801994z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Conformational Dynamics of mRNA upon AtGRP7 Binding Studied by Fluorescence Correlation Spectroscopy

Abstract: The clock-regulated RNA recognition motif (RRM)-containing protein AtGRP7 (Arabidopsis thaliana glycine-rich RNA-binding protein) influences the amplitude of its transcript oscillation at the post-transcriptional level. This autoregulation relies on AtGRP7 binding to its own pre-mRNA. The sequence and structural requirements for this interaction are unknown at present. In this work, we used photoinduced electron transfer fluorescence correlation spectroscopy (PET-FCS) as a novel technique to study the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…This is the case for the cysteine-rich domain of AtGRP3 responsible for interaction with AtWAK1, 19 and the RNA-binding sequences of Class IV GRPs. [21][22][23][24][25][26][27][28][32][33][34] On the other hand, Class I GRPs that present no additional characterized domain besides a signal peptide presented functional properties. PvGRP1.8 and AtGRP5 are composed of nothing but a glycinerich domain suggesting that this domain is responsible for their function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case for the cysteine-rich domain of AtGRP3 responsible for interaction with AtWAK1, 19 and the RNA-binding sequences of Class IV GRPs. [21][22][23][24][25][26][27][28][32][33][34] On the other hand, Class I GRPs that present no additional characterized domain besides a signal peptide presented functional properties. PvGRP1.8 and AtGRP5 are composed of nothing but a glycinerich domain suggesting that this domain is responsible for their function.…”
Section: Discussionmentioning
confidence: 99%
“…AtRBG7 preferentially binds to ssRNA if it is fully stretched rather than to molecules presenting a stable secondary structure. 26 AtRBG7 binds to its own pre-mRNA generating an alternativelly spliced form that is rapidly degraded. A mutation on a conserved arginine of the RRM motif of AtRBG7 prevents this autoregulation.…”
Section: Function Of Grps In Cold Stress Is Not Limited To the Presenmentioning
confidence: 99%
“…Interaction between Nt RRM and ssDNA or RNA was studied using a 6-nt probe (5′-TTCTGG-3′ for DNA and 5′-UUCUGG-3′ for RNA; Eurofins MWG Operon) that was previously identified as a minimum binding sequence for homologue At GR-RBP7 (34). The RNA and DNA probes were either ordered as HPLC purified (RNA) or purified over a G10 column (DNA), lyophilized and dissolved in NMR buffer to a stock concentration of 0.18 mM (RNA) or 1 mM (DNA).…”
Section: Methodsmentioning
confidence: 99%
“…Studying interactions between a RNA-binding protein (Arabidopsis thaliana glycine-rich RNA-binding protein, AtGRP7) and specific RNA sequences, we demonstrated that changes in conformational dynamics of the RNA upon protein binding can be observed and analyzed as reporter for the binding process. [93] Such experiments yield structural information about various binding modes but also serve as diagnostic tool to detect protein-nucleotide [93] as well as protein-protein [94] interactions.…”
Section: Conformational Dynamics Of Oligonucleotides and Biomolecularmentioning
confidence: 99%